Endoscopic DCR using bipedicled interlacing mucosal flaps. (8th August 2017) - Mueller, Sarina K.; Freitag, Suzanne K.; Lefebvre, Daniel R.; Bleier, Benjamin S.
Abstract : Objective: Obstruction of the nasolacrimal duct is a relatively common condition that affects patients of all ages, races, and sexes. The surgical gold standard for complete nasolacrimal duct obstruction and dacryocystitis is dacryocystorhinostomy (DCR). The purpose of this study was to describe a novel, bipedicled interlacing mucosal sparing flap technique for endoscopic DCR (eDCR). Methods: A posteriorly based mucosal flap over the fundus is combined with a novel, anteriorly based mucosal flap over the intraosseus portion of the nasolacrimal duct (NLD). This exposes a wide area of the maxillary bone, allowing for exposure and identification of the NLD/sac complex in a safer, more inferior position. The interlacing mucosal flaps may be replaced at the conclusion of the procedure, thereby minimizing bone exposure and maintaining excellent long‐term patency. Results: The authors have utilized this technique in 55 procedures with 100% positive identification of the NLD and lacrimal sac, 0% complication rate, 100% anatomical patency rate, and 96.4% success rate after a minimal follow‐up of 6 months. Discussion: The bipedicled interlacing flap technique for eDCR provides for safe and reproducible identification of the NLD and lacrimal sac while minimizing bone exposure and restenosis rate. Conclusion: The bipedicled interlacing flap technique for eDCR provides for safe and reproducible identification of the NLD and lacrimal sac while minimizing bone exposure and restenosis rate. Level of Evidence: NA. Laryngoscope, 128:794–797, 2018